Ferno : the fire dragon - Blade, Adam.; Tucker, Ezra N. (New York : Scholastic, 2007)
"One boy's journey to help his village becomes a quest to save the kingdom. Strange things are happening in Tom's village. First, the horses were attacked. Then, the river dried up. Now, the last of thre crops has mysteriously burned. Everyone is terrified. But Tom isn't afraid. He's always dreamed of a quest -- a real quest! -- and vows to go to the king and bring help for them. But Tom soon learns that his village is not the only one in danger. There is terrible trouble all throughout the kingdom, and hope is nearly lost. That is, until Tom is sent on the greatest quest of all -- the Beast Quest"--P. [4] of cover.
"A Little Apple paperback."
Keywords: Dragons -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Boys -- Juvenile fiction; Fantasy fiction; Adventure fiction